(untitled) (مجلة العلوم الشاملة, 2025)
This paper investigates what drives patients’ acceptance of EHR-enabled e-health services in Libya. A cross-sectional survey was conducted at Tripoli Central Hospital in June 2017 using a structured 44-item questionnaire, and 70 respondents provided usable data (N = 70). Patient ac-ceptance (the dependent variable) was measured as willingness to use online health services and applications, such as booking appointments online, accessing laboratory results online, and receiving medical advice or prescriptions online. Three determinants were examined: privacy-related percep-tions about sharing personal information, perceptions of online health-information exchange, and the patient–doctor relationship. Results show strong positive associations between acceptance and all three determinants. When the determinants were analyzed jointly using a standardized regres-sion model, the patient–doctor relationship and perceived online exchange remained the strongest contributors to acceptance, while privacy-related perceptions added less unique explanatory power once overlap among determinants was considered. The findings suggest that improving trust in clin-ical relationships and strengthening credible, secure information exchange are central to increasing patient acceptance of e-health services in the Libyan healthcare context.